INDONESIA'S EFFORTS IN G 20 SUMMIT PITTSBURGH 2009 TO OVERCOME THE IMPACTS OF GLOBAL ECONOMIC CRISIS IN SOUTHEAST ASIA REGION - Yolla Ananda P (2010)
ABSTRACT International relations are important part in globalization era. Each of states in the world cannot fulfill they own desire without support from of other states. The relation among core state, periphery, and semi periphery states is one of the examples of interdependency in the world nowadays, especially there is interdependency between developed states and developing states. In the complex interdependency, regardless the "rank" of states they have common goal to improve their economi